2020
DOI: 10.1371/journal.pone.0235826
|View full text |Cite
|
Sign up to set email alerts
|

The impact of physician education regarding the importance of providing complete clinical information on the request forms of thrombophilia-screen tests at Tygerberg hospital in South Africa

Abstract: Background Thrombophilia-screen tests are specialised haemostasis tests that are affected by numerous unique patient variables including the presence of acute thrombosis, the concomitant use of medication and patient demographics. Complete information on the request form is therefore crucial for the haematological pathologist to make patient-specific interpretation of patients' results. Objectives To assess the completeness of thrombophilia-screen test request forms and determine the impact of provision of inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…These studies identified the impact of such training by determining sample rejection rates before and after intervention. A recent quasi-experimental study performed at TAH revealed that physician education failed to improve the quality and comprehensiveness of thrombophilia screening test request forms [ 27 ]. A new, amended request form, electronic test ordering and continued physician education was proposed as solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies identified the impact of such training by determining sample rejection rates before and after intervention. A recent quasi-experimental study performed at TAH revealed that physician education failed to improve the quality and comprehensiveness of thrombophilia screening test request forms [ 27 ]. A new, amended request form, electronic test ordering and continued physician education was proposed as solution.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively these studies illustrated that the quality of coagulation samples is sensitive to various technical and time variables. Deficiencies in the pre-analytical phase and exploring avenues of remedial action to reduce the incidence of pre-analytical errors have also been studied [ 23 27 ]. However, a critical analysis concerning the accuracy with which pre-analytical errors are identified in the haemostasis laboratory is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have shown that it has become essential to use community-based approaches for reaching out individual households and dwelling units. Abdullah, Jafta, and Chapanduka (2020) have shown that adequately qualified health professionals are essential for providing reliable and efficient health care services visiting health care facilities. The authors have shown that it is essential for health care facilities to have enough number of adequately qualified health workers who can accurately perform laboratory tests and conduct diagnostic and physical examinations on visiting patients.…”
Section: Literature Reviewmentioning
confidence: 99%